2003
DOI: 10.1177/002199803035186
|View full text |Cite
|
Sign up to set email alerts
|

S2-Glass/Epoxy Polymer Nanocomposites: Manufacturing, Structures, Thermal and Mechanical Properties

Abstract: This paper is primarily focused in studying the effects of nanoclay particles such as montmorillonite on improving mechanical and thermal properties of fiber reinforced polymer matrix composite materials. Basic correlations between polymer morphology, strength, modulus, toughness, and thermal stability of thermoset nanocomposites were investigated as a function of layered silicate content. S2-glass/epoxy-clay nanocomposites were manufactured through an affordable vacuum assisted resin infusion method (VARIM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
142
5
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(159 citation statements)
references
References 10 publications
11
142
5
1
Order By: Relevance
“…Kornmann et al 25 showed that there is a marginal improvement of 6% in the flexural modulus of epoxy composites after dispersion of 2.0 wt% clay particles, and similar behavior was also observed by Haque et al 26 On the basis of the improvements in Young's modulus and the flexural modulus, it can be concluded that Cloisite 30B is more compatible with the epoxy matrix than Cloisite 15A; Cloisite 30B improves Young's modulus by 147% and the flexural modulus by 133%. This may be result from a maximum enhancement in the interlayer spacing of Cloisite 30B powder in comparison with Cloisite 15A, as is further supported in Table 4.…”
Section: Resultssupporting
confidence: 66%
“…Kornmann et al 25 showed that there is a marginal improvement of 6% in the flexural modulus of epoxy composites after dispersion of 2.0 wt% clay particles, and similar behavior was also observed by Haque et al 26 On the basis of the improvements in Young's modulus and the flexural modulus, it can be concluded that Cloisite 30B is more compatible with the epoxy matrix than Cloisite 15A; Cloisite 30B improves Young's modulus by 147% and the flexural modulus by 133%. This may be result from a maximum enhancement in the interlayer spacing of Cloisite 30B powder in comparison with Cloisite 15A, as is further supported in Table 4.…”
Section: Resultssupporting
confidence: 66%
“…A more comprehensive study on clay-epoxy nanocomposites was undertaken by Haque and Shamsuzzoha (2003), which evaluated both mechanical and thermal properties. Their main conclusions were that thermo-mechanical properties mostly increase with low clay loadings (1-2% in Latin American Journal of Solids and Structures 11(2014) 245 -259 weight), but decrease with higher clay loadings (≥ 5% in weight).…”
Section: Introductionmentioning
confidence: 99%
“…Hence there is a need to explore further investigation. Haque 13 , et al fabricated glass/epoxy nanocomposites through an affordable vacuum assisted resin infusion method (VARIM). They showed that significant improvements in mechanical and thermal properties of conventional fiber reinforced composites with low loading of organo silicate nanoparticles.…”
Section: Introductionmentioning
confidence: 99%